Bunu cilt 26 makalesi için kullanalim - Çorak, Tuncay (Journal of Dependence, 2025)
Objective: The literature has extensively examined the relationship between self-esteem and smartphone addiction. However, few studies focus on the psychological mechanisms underlying this relationship. This study aims to evaluate the connection between self-esteem and smartphone addiction and explore the mediating effects of psychological symptoms in this relationship. Method: A cross-sectional and descriptive study was conducted using a convenience sampling method. The sample included 646 participants. Data were collected through the "Rosenberg Self-Esteem Scale," the "Depression Anxiety Stress Scale," the "Smartphone Addiction Scale," and a "Demographic Information Form." Pearson correlation analysis was used to evaluate the relationships between variables, while mediation analysis assessed the indirect effects of psychological symptoms on the relationship between self-esteem and smartphone addiction. Results: Self-esteem, anxiety, and stress were found to predict smartphone addiction. Anxiety and stress significantly mediated the relationship between self-esteem and smartphone addiction, whereas depression did not show a significant mediating effect. Conclusion: This study highlights the importance of psychological symptoms in the complex interplay of factors contributing to smartphone addiction. It provides new evidence that can inform interventions in this area and expands the theoretical understanding of how smartphone addiction develops.